Analysis of Road Condition Assessment Using The Surface Distress Index (SDI) Method and Estimation of Road Maintenance Costs For The Durenan-Prigi Road Section (Link 006) - Muhammad Fareza Akbar; Risma Marleno; Wateno Oetomo (Journal of Social Research, 2025)
The Durenan - Prigi road section is a 30.4 km long road that is authorized by the East Java Provincial Government, this road is one of the access roads to Prigi Beach, Mutiara Beach and other tourist attractions in Trenggalek Regency. The road that is the access to the tour certainly requires care and maintenance to always be in steady condition and does not reduce the comfort of road users. Factors that cause damage include traffic load factors, soil condition factors, weather, rain, drainage channel factors and so on. In monitoring road conditions, there is a road condition assessment, namely the Surface Distress Index (SDI) method. The objective of this research is to evaluate the condition of the Durenan-Prigi road section using the Surface Distress Index (SDI) method to assess its current state, determine necessary maintenance actions, and estimate the required budget for its upkeep. The SDI method is a method of assessing the condition of the road surface by making visual observations. The SDI method has four types of damage in assessing road conditions with four categories of road condition assessment results. The Durenan - Prigi road section has an average SDI value of 11.89 with an assessment of "Good" condition.  Nevertheless, maintenance is still required with an estimated budget of Rp2,596,960,786.27. The budget includes three main components, namely type 3 emulsified asphalt coating (CQS-1h) amounting to Rp2,392,020,512.39, repairing the cold-applied asbuton mixture amounting to Rp160,955,321.83, and closing type 1 cracks (crack width 0.20-0.50 cm) amounting to Rp43,984,952.06.